Artificial intelligence in behavioral and mental health care - Luxton, David D. (Academic Press, 2016)
Summarizes recent advances in artificial intelligence as it applies to mental health clinical practice. This book will be of use to mental health practitioners interested in learning about or incorporating AI advances into their practice and for researchers interested in a comprehensive review of these advances in one source.